The effects of short-term resistance program on vertical jump ability in elite male volleyball players during the competition season (Efectos de un entrenamiento de fuerza de corta duración sobre la capacidad de salto vertical en jugadores de voleibol de - Sánchez Moreno, Miguel; García Asencio, Carlos; González Badillo, Juan José (Retos, 2014)
The aim of this study was to describe the effects of 6 weeks of combined strength and jump training which incorporated moderate loads and high intensity contractions on the vertical jump ability (VJ), loaded jumps and velocity of execution in full squat in a group of professional male volleyball players during the competition season. It was hypothesized that the VJ improved by cross combined strength and jump training both characterized by high velocity of execution (>1m/s). The participants in this study were twelve players who competed in the first national division of the Spanish National League during the 2011-2012 season. The neuromuscular performance was estimated by unloaded (CMJ) and loaded countermovement jumps (CMJloaded) height (cm); and by velocity of displacement in the concentric phase of full squat (FS) (m/s). There was a significant increase in CMJ and CMJloaded after 6-week of training (5%, p<0.01; and 5.7%, p<0.05; respectively). These changes were accompanied by a small and moderate value of Effect Size (0.47, and 0.67; respectively). No significant differences were observed for velocity of displacement in FS. The linear correlation analysis showed a single moderate correlation statistically significant between the changes in CMJ-CMJloaded and CMJ-FS (r=0.62 and r=0.59, p<0.05; respectively). Albeit speculative, our results suggest that the use of moderate loads could be enough to improve the vertical jump performance, since in our study a load equivalent to 60% 1RM in the FS was not exceeded and jumping exercises were performed with light loads. Keywords: Resistance training; Plyometric exercise; Vertical jump; Lower Extremity, Velocity, Strength. Resumen: El objetivo de este estudio fue describir los efectos de 6 semanas de entrenamiento combinado de fuerza y salto, el cual incorpora cargas moderadas e intensidades de contracción altas, sobre la capacidad de salto vertical, saltos con cargas y la velocidad de ejecución en el ejercicio de sentadilla en un grupo de jugadores profesionales de voleibol durante la temporada de competición. Se estableció la hipótesis de que el salto vertical mejoro por el uso combinado de entrenamiento de fuerza y salto, ambos caracterizados por una alta velocidad de ejecución (>1m/s). El rendimiento neuromuscular fue estimado por la altura (cm) del salto sin cargas (CMJ), salto con cargas (CMJloaded), y por la velocidad (m/s) de desplazamiento en la fase concéntrica en la sentadilla completa (FS). Tuvo lugar un incremento significativo en CMJ y CMJloaded después de 6 semanas de entrenamientos (5%, p<0.01; y 5.7%, p<0.05; respectivamente). Estos cambios fueron acompañados por un valor de Tamaño del Efecto pequeño y moderado (0.47, and 0.67; respectivamente). No se observaron diferencias significativas en la velocidad de desplazamiento en FS. El análisis de correlación lineal mostró una correlación moderada estadísticamente significativa entre los cambios en CMJ-CMJloaded y CMJ-FS (r=0.62; y r=0.59, p<0.05; respectivamente). Aunque algo especulativo, nuestros resultados sugieren que el uso de cargas moderadas podría ser suficiente para mejorar el rendimiento del salto vertical, ya que en nuestro estudio no se excedió una carga equivalente al 60% de 1RM en FS y los ejercicios de saltos también fueron realizados con cargas ligeras. Palabras claves: Entrenamiento con resistencias, ejercicios pliométricos, salto vertical, extremidad inferior, velocidad, fuerza.